Shape‐Customizable Macro‐/Microporous Carbon Monoliths for Structure‐to‐Functionality CO2 Adsorption and Novel Electrical Regeneration. Issue 10 (14th August 2017) - Wang, Mei; Li, Yuexing; Pan, Min; Jia, Xianfeng; Yin, Di; Long, Donghui; Wang, Jitong; Qiao, Wenming; Ling, Licheng
Abstract: Potential of porous carbons for practical applications is often limited by their intrinsic fragility and poor processability. Here, a facile approach to fabricate hierarchically macro‐/microporous carbon monolith (CM) with high strength and integrated structure is developed, which offers great possibilities for structure‐to‐functionality applications. Through a fiber‐reinforced sol–gel process and an ambient pressure drying approach, aerogel‐like CMs can be designed and fabricated in customizable forms. In particular, a novel scroll‐type carbon monolith (S‐CM) is constructed, which can mimic a roll‐to‐roll tube reactor and thus avoid the packing problems arising from the granules or powders of conventional activated carbons. The resulting CM exhibits a high CO2 adsorption capacity of 15.9 mmol g −1 at 25 bar and a breakthrough capacity of 1 mmol g −1 at 1 bar. Moreover, owing to the integrated structure and good electrical conductivity, the scroll‐type S‐CM can be easily regenerated by employing a low‐energy electrothermal desorption technique. The specialized design of the CMs should fulfill industrial directives and may provide an access route to more efficient porous carbons for structure‐oriented and process‐intensified applications. Abstract : A fiber‐reinforced sol–gel approach is developed to fabricate hierarchically macro‐/microporous carbon monolith (CM) with high strength and integrated structure. In particular, CM with scroll shape is constructed, which can mimic a roll‐to‐roll tube reactor structure, allowing both radial and axial gas fluidic uniformity for process‐intensified CO2 adsorption and endowing a novel electrothermal regeneration technique for low‐energy adsorption–desorption cycles.